2017
DOI: 10.1080/17451000.2016.1248849
|View full text |Cite
|
Sign up to set email alerts
|

Relative growth and size at onset of sexual maturity of the brown crab, Cancer pagurus in the Isle of Man, Irish Sea

Abstract: In this study, the relative growth, size-weight relationships and size at onset of maturity of the brown crab Cancer pagurus were investigated in the Isle of Man. For the analyses of relative growth and size at onset of maturity, the samples were collected seasonally between autumn 2012 and spring 2013 using several methods: pot surveys, dredge and trawl surveys, market surveys and shore surveys. Results showed that allometric growth occurred in the chelipeds of males (n = 87) and in the abdomen of females (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
(45 reference statements)
3
11
0
Order By: Relevance
“…The strong linear relationship between weight and fecundity indicated that heavier females tended to produce more eggs. Similar results have been reported for other crustaceans such as Cherax quadricarinatus (Öndes, Kaiser & Murray, 2017) and Oziothelphusa senex senex (Swetha, Girish & Reddy, 2015). Moreover, it was noteworthy that fecundity started to decrease when cephalothorax width was over 23 mm.…”
Section: Discussionsupporting
confidence: 89%
“…The strong linear relationship between weight and fecundity indicated that heavier females tended to produce more eggs. Similar results have been reported for other crustaceans such as Cherax quadricarinatus (Öndes, Kaiser & Murray, 2017) and Oziothelphusa senex senex (Swetha, Girish & Reddy, 2015). Moreover, it was noteworthy that fecundity started to decrease when cephalothorax width was over 23 mm.…”
Section: Discussionsupporting
confidence: 89%
“…Given that growth and maturity may vary depending on environmental factors and population density, it is important that estimates of size-at-maturity are updated regularly over time and are stock-specific. For widely distributed species such as brown crab, these regional variations in biology should be taken into account when setting MLS (Bennett, 1995;Öndes et al, 2017). A number of studies have been carried out on brown crab maturity around the British Isles and more widely across Europe, predominantly based on gonadal maturity, morphometric characters or presence of sperm plugs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on this species in Scotland have been limited to Shetland and Orkney (Tallack, 2007;Haig et al, 2016). There have also been studies in Bay of Biscay (Le Foll, 1984), Norway (Haig et al, 2016;Bakke et al, 2018), Ireland (Tully et al, 2006), Skagerrak and Kattegat (Ungfors, 2007), Wales (Haig et al, 2016), Isle of Man (Haig et al, 2016;Öndes et al, 2017), east coast of England and English Channel (Smith, 2010;Haig et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the overall dimension of AW in Scylla females once they reach sexual maturity, i.e., become more globular and dark in color, are expected and has been used as a key factor to determine size at sexual maturity in wild populations of Scylla spp. ( Overton & Macintosh, 2002 ; Waiho et al, 2016 ) and other brachyuran species ( Mura, Orrù & Cau, 2005 ; Williner et al, 2014 ; Öndes, Kaiser & Murray, 2017 ). Unlike females, the AW of males retains almost the same colouration and shape since juvenile stages ( Waiho, Fazhan & Ikhwanuddin, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike females, the AW of males retains almost the same colouration and shape since juvenile stages ( Waiho, Fazhan & Ikhwanuddin, 2016 ). Variation in AW between sexes is common in most brachyuran species ( Haefner Jr, 1990 ; Josileen, 2011 ; Davanso et al, 2016 ; Öndes, Kaiser & Murray, 2017 ). The broadening of the abdomen in Scylla females occurs when they reach sexual maturity ( Waiho et al, 2016 ) and is linked with reproductive functions such as attachment of eggs and incubation.…”
Section: Discussionmentioning
confidence: 99%